Responsiveness Index versus the RASS-Based Method for Adjusting Sedation in Critically Ill Patients - Johanna E. Wennervirta; Mika O. K. Särkelä; Markus M. Kaila; Ville Pettilä (Critical Care Research and Practice)
Background. Sedation of intensive care patients is needed for patient safety, but deep sedation is associated with adverse outcomes. Frontal electromyogram-based Responsiveness Index (RI) aims to quantify the level of sedation and is scaled 0–100 (low index indicates deep sedation). We compared RI-based sedation to Richmond Agitation-Sedation Scale- (RASS-) based sedation. Our hypothesis was that RI-controlled sedation would be associated with increased total time alive without mechanical ventilation at 30 days without an increased number of adverse events. Methods. 32 critically ill adult patients with mechanical ventilation and administration of sedation were randomized to either RI- or RASS-guided sedation. Patients received propofol and oxycodone, if possible. The following standardized sedation protocol was utilized in both groups to achieve the predetermined target sedation level: either RI 40–80 (RI group) or RASS −3 to 0 (RASS group). RI measurement was blinded in the RASS group, and the RI group was blinded to RASS assessments. State Entropy (SE) values were registered in both groups. Results. RI and RASS groups did not differ in total time alive in 30 days without mechanical ventilation (p=0.72). The incidence of at least one sedation-related adverse event did not differ between the groups. Hypertension was more common in the RI group (p=0.01). RI group patients were in the target RI level 22% of the time and RASS group patients had 57% of scores within the target RASS level. The RI group spent significantly more time in their target sedation level than the RASS group spent in the corresponding RI level (p=0.03). No difference was observed between the groups (p=0.13) in the corresponding analysis for RASS. Propofol and oxycodone were administered at higher RI and SE values and lower RASS values in the RI group than in the RASS group. Conclusion. Further studies with a larger sample size are warranted to scrutinize the optimal RI level during different phases of critical illness.